Organizational culture, social capital, and emergency capacity in primary healthcare institutions: A cross-sectional structural equation modeling study comparing ordinary and older communities - Xianhong Huang; Jiamin Tang; Jie Jia; Ling Zou; Kaidi Sun; Zhengnan Meng; Xiaoting Zhang (PLoS ONE, 2026)
The emergency capacity of primary healthcare institutions is critical to the effectiveness of grassroots emergency management. This study examines the relationships among organizational culture, social capital, and the emergency capacity of primary healthcare institutions using a structural equation modeling approach. A questionnaire survey was conducted among healthcare professionals, yielding 983 valid responses for analysis. The results indicate that organizational culture, as well as structural, relational, and cognitive dimensions of social capital, are significantly associated with the emergency capacity of primary healthcare institutions within the model. In addition, social capital demonstrates mediating roles in the relationship between organizational culture and emergency capacity. Multi-group structural equation modeling further reveals variations across community types: relational social capital shows stronger associations with emergency capacity in ordinary communities, whereas structural social capital is more prominent in older communities. These findings provide empirical evidence on how organizational culture and social capital are linked to emergency capacity in primary healthcare settings, highlighting the importance of both internal cultural development and external social resources in different phases of emergency management.